Analysis of preservice mathematics teachers’ quantitative problem solving ability in solving PISA based tasks: a polya framework perspective - Suratman, Dede; Yusmin, Edy; Meldi, Nadya Febriani; Wahyuningsih, Dian (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to analyze the quantitative problem-solving ability of preservice mathematics teachers in solving PISA-based tasks across different contexts and proficiency levels using Polya’s four-stage problem-solving framework. Method: A qualitative descriptive design was employed to examine students’ reasoning processes through written responses and in-depth interviews. The participants were preservice mathematics teachers who had completed most of the core mathematics courses in their teacher education program. The research instrument consisted of three PISA-like tasks representing personal, socio-economic, and scientific contexts with cognitive demands corresponding to PISA Levels 6, 5, and 4. Students’ solutions were analyzed using Polya’s stages: understanding the problem, devising a plan, carrying out the plan, and verifying the solution. Based on their performance, participants were categorized into high, medium, and low groups to identify patterns of reasoning and problem-solving strategies. Findings: The results show that the overall numeracy ability of preservice mathematics teachers remains in the medium–low category with an average score of 44.10 and considerable variation among participants. High-performing students demonstrated stronger abilities in mathematical modeling, proportional reasoning, and variable identification, particularly when solving higher-level PISA tasks. In contrast, students in the medium and low groups relied primarily on procedural calculations with limited conceptual understanding of relational structures and representations. Although many students produced correct answers for Level 4 tasks, their solutions were often procedural rather than conceptually grounded. Significance: The findings indicate a gap between preservice teachers’ current quantitative literacy and the competencies required for PISA-type mathematical problem solving. Strengthening quantitative reasoning through authentic contexts, mathematical modeling, and structured reflection is therefore essential in mathematics teacher education programs.